Digest: Resolving phylogenomic conflicts in characiform fishes†. (25th January 2019) - Montero‐Mendieta, Santiago; Dheer, Arjun
Abstract: How can taxonomists best resolve the challenge of curating and analyzing large phylogenomic datasets that produce incongruent but highly supported topologies? Betancur‐R et al. used a recently established hypothesis‐testing procedure on a large dataset of genes and species to study the evolutionary relationships of characiform fishes, finding that past conclusions of non‐monophyly may have been problematic and establishing monophyly with high confidence. The new findings highlight the importance of using dense taxon sampling to resolve conflicting relationships with phylogenomic data.